Värme- & fuktegenskaper hos biobaserade isoleringsmaterial - Bálint Palmgren,Oscar (2019)
To meet national and international emission targets, the Swedish building sector needs to drastically reduce its carbon dioxide emissions, and to do so, a change in building techniques and materials is needed. Bio-based materials contribute to less emissions than conventional materials, like steel and concrete, but remain rather unknown to modern building sciences. This study aimed to increase knowledge about these materials, by measuring heat and moisture characteristics according to the Transient Plane Source method, the development of sorption isotherms, and finally simulating the impact of these materials on the hygrothermal attributes of a building envelope, all in comparison to conventional mineral wool. It was found that the biobased materials had a higher thermal conductivity and specific heat capacity, but lesser thermal diffusivity than mineral wool. They were also a lot more hygroscopic. Finally, it was concluded that these hygroscopic, biobased insulation materials could be used as an alternative for mineral wool in conventional Swedish building envelope systems, but were subject to mold and rot in more unconventional designs.
Keywords: Bio; insulation; hempfibre; woodfibre; mineral wool; heat; moisture; TPS; Transient Plance Source; heat conductivity; specific heat capacity; sorption; absorption